Performance evaluation of some MPI implementations on workstation clusters - Nupairoj, N.; Ni, L.M. (Proceedings of the 1994 Scalable Parallel Libraries Conference, October 12-14, 1994, Mississippi State University, Mississippi, 1994)
Message Passing Interface (MPI) is an attempt to standardize the communication library for distributed-memory computing systems. Since the release of the recent MPI specification, several MPI implementations have been made publicly available. Different implementations employ different approaches, and thus, the performance of each implementation may vary. Since the performance of communication is extremely crucial to message-passing based applications, selecting an appropriate MPI implementation becomes critical. Our study is intended to provide a guideline on how to perform such a task on workstation clusters which are known to be an economical and effective platform in high performance computing. We investigate several MPI aspects including its functionalities and performance. Our results also point out the strength and weakness of each implementation on our experimental system.< >